Anaesthetic Management of a Patient with Down Syndrome VSD, ASD & PDA in Pediatric Cardiac Surgery Department, Dhaka Shishu Hospital (Journal of the Bangladesh Society of Anaesthesiologists, 2020)
Down syndrome or trisomy 21 is a condition where extra genetic material causes mental and physical delays and deficits. It affects 1 in every 650 babies. Abnormalities of the cardiovascular system are common in down syndrome. Approximately half of all infants born with down syndrome have a heart defect. The most common heart defects in down syndrome are the following: atrioventricular septal defect (45%), ventricular septal defect (35%), atrial septal defects (8%) and patent ductus arteriosus (7%), tetralogy of Fallots (4%). A Two years one-month-old baby was admitted in cardiac surgery department of Dhaka Shishu Hospital, with the diagnosis of Down syndrome with VSD,ASD& PDA with moderate pulmonary arterial hypertension. Clinical examination revealed diastolic murmur over mitral area. The child was treated with face musk oxygen, diuretics and digoxin and was stabilized medically and then was selected for surgery. We used balanced anesthetic technique using oxygen, air, fentanyl, midazolam and vecuronium. Patient was operated under cardiopulmonary bypass (CPB) with moderate hypothermia. Patient tolerated the whole procedure well and was ventilated electively for 4hrs in the intensive care unit. He was discharged on the 8thpostoperative day.Journal of Bangladesh Society of Anaesthesiologists 2015; 28(1): 39-42